2011
DOI: 10.1007/s00595-010-4501-z
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic hernia of a retrosternal colonic graft after esophagectomy: Report of a case

Abstract: We report a case of intrathoracic herniation of the colonic interposition pulled up through the retrosternal space after subtotal esophagectomy for esophageal cancer. The patient, a 68-year-old man, presented with progressive dysphagia about 1 year after this operation. We performed left thoracotomy and laparotomy, which revealed the reconstructed colon herniating into the left thoracic cavity through a large defect in the left mediastinal pleura. The redundant colon was resected, and the colonic graft was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…However, most sites of internal hernias in Roux-Y reconstruction after total gastrectomy include a transverse mesocolon defect, such as Petersen's space and a jejunojejunostomy defect [ 6 ]. With regard to case reports of intrathoracic hernia, there are a few reports after a procedure for esophageal cancer [ 8 , 11 ], but there are no reports after total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, most sites of internal hernias in Roux-Y reconstruction after total gastrectomy include a transverse mesocolon defect, such as Petersen's space and a jejunojejunostomy defect [ 6 ]. With regard to case reports of intrathoracic hernia, there are a few reports after a procedure for esophageal cancer [ 8 , 11 ], but there are no reports after total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report to document such an event. Only a few case reports have documented intrathoracic herniation of reconstructed organs [5,9] . For example, Takayama et al [5] reported a case of an intrathoracic herniation of a retrosternal colonic graft following esophagectomy, which presented with progressive dysphagia approximately 1 year following esophagectomy, despite an uneventful clinical course in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few case reports have documented intrathoracic herniation of reconstructed organs [5,9] . For example, Takayama et al [5] reported a case of an intrathoracic herniation of a retrosternal colonic graft following esophagectomy, which presented with progressive dysphagia approximately 1 year following esophagectomy, despite an uneventful clinical course in the early postoperative period. In this earlier case, the authors performed left thoracotomy and laparotomy, which revealed that the reconstructed colon had herniated into the left thoracic cavity through a large defect in the left mediastinal pleura.…”
Section: Discussionmentioning
confidence: 99%
“…The retrosternal route is one reconstruction route that may be used after esophagectomy. Intrathoracic herniation of reconstructed organs was reported by Takayama et al [3] and Uemura et al [4], but no reports have described the incarceration of intestinal tissues other than reconstructed organs in the retrosternal space and thoracic cavity. We herein report three cases of internal hernia to the retrosternal space (hereafter called retrosternal hernia) after MIE.…”
Section: Introductionmentioning
confidence: 99%